‘Praise the Lord, All you Gentiles’: The Encoded Audience of Romans 15.7-13 - Das, A. Andrew (Journal for the study of the New Testament, 2011)
Romans 15.7-13 addresses an encoded gentile audience. The best solution to the syntactical challenges posed by 15.8-9a places the focus on the gentiles who now glorify God as a result of Christ’s servanthood. Paul’s identification of the Jewish people as ‘the circumcision’, a negative category earlier in the letter (2.25—3.30; 9.18), is hardly apt if he is also addressing Jewish Christians. Romans 15.6-9a links the Roman audience’s mutual welcoming ‘for the glory of God’ to the gentiles’ glorifying God. The Scripture citations in 15.9b-12 remain riveted on God’s purpose for the gentiles and address the Romans as gentiles. Romans 15.12-13 links the Roman audience’s hope with the hope of the gentiles. The preceding context identifies the ‘weak’ not as Jews but by customs that were popular among gentile sympathizers. Romans 15.14-21 conforms to Paul’s pattern elsewhere in the letter of identifying the encoded audience as the recipients of his gentile ministry.